Common Risk Factors Add to Inherited Thrombophilia to Predict Venous Thromboembolism Risk in Families - Suchon, Pierre; Resseguier, Noemie; Ibrahim, Manal; Robin, Alexia; Venton, Geoffroy; Barthet, Marie-Christine; Brunet, Dominique; Saut, Noemie; Alessi, Marie-Christine; Trégouët, David A.; Morange, Pierre E. (TH Open, 2019)
The clinical venous thromboembolism (VTE) pattern often shows wide heterogeneity within relatives of a VTE-affected family, although they carry the same thrombophilia defect. It is then mandatory to develop additional tools for assessing VTE risk in families with thrombophilia. This study aims to assess whether common environmental and genetic risk factors for VTE contribute to explain this heterogeneity. A total of 2,214 relatives from 651 families with known inherited thrombophilia were recruited at the referral center for thrombophilia in Marseilles, France, from 1986 to 2013. A thrombophilia screening was systematically performed in all included relatives. According to the severity of the thrombophilia defect, individuals were split into three groups: no familial defect, mild thrombophilia, and severe thrombophilia. In addition, common genetic factors (ABO blood group and 11 polymorphisms selected on the basis of their association with VTE in the general population) were genotyped. Furthermore, body mass index and smoking were collected. VTE incidence was 1.74, 3.64, and 6.40 per 1,000 person-years in individuals with no familial defect, mild thrombophilia, and severe thrombophilia, respectively. Five common risk factors were associated with VTE in this population: obesity, smoking, ABO blood group, and F11_rs2036914 and FGG_rs2066865 polymorphisms. These common factors were then included into a three-level risk score. The score was highly efficient for assessing VTE risk in mild thrombophilia patients by identifying two groups with different VTE risk; individuals with low score had the same risk as individuals with no familial defect whereas individuals with high score had the same risk as individuals with severe thrombophilia. An overall score including the five items plus the thrombophilia status was built and displayed an area under the receiver operating characteristic curve of 0.702 for discriminating VTE and non-VTE relatives. In conclusion, integrating common environmental and genetic risk factors improved VTE risk assessment in relatives from families with thrombophilia.
Keywords: family medical history; single nucleotide polymorphism; risk assessment; thrombophilia; venous thromboembolism